SUMOylation as a Therapeutic Target for Myocardial Infarction - Zhao, Wei; Zhang, Xiuying; Rong, Jianhui (Frontiers in Cardiovascular Medicine, 2021)
Myocardial infarction is a prevalent and life-threatening cardiovascular disease. The existing interventional strategies mainly target the resuming of coronary reperfusion while few are designed to ameliorate the pathology of heart diseases via targeting the post-translational modifications of those critical proteins. Small ubiquitin-like modifier (SUMO) proteins are recently discovered to form a new type of protein post-translational modifications (PTMs), known as SUMOylation. SUMOylation and deSUMOylation are dynamically balanced in the maintenance of various biological processes including cell division, DNA repair, epigenetic transcriptional regulation, and cellular metabolism. Importantly, SUMOylation plays a critical role in the regulation of cardiac functions and the pathology of cardiovascular diseases, especially in heart failure and myocardial infarction. This review summarizes the current understanding on the effects of SUMOylation and SUMOylated proteins in the pathophysiology of myocardial infarction and identifies the potential treatments against myocardial injury via targeting SUMO. Ultimately, this review recommends SUMOylation as a key therapeutic target for treating cardiovascular diseases.